Nestin is essential for cellular redox homeostasis and gastric cancer metastasis through the mediation of the Keap1–Nrf2 axis - Jing Lv (BMC, 2021)
Abstract Background Gastric cancer (GC) is a common malignancy of the digestive system. Antioxidant activity is regarded as a possible mechanism in ectopic cancer. Hence, oxidative stress regulation is being evaluated for cancer treatment. Previous research has demonstrated that Nestin is associated with antioxidative resistance via its modulation of the Kelch-like ECH-associated protein 1 (Keap1)–nuclear factor erythroid 2-related factor 2 (Nrf2) pathway. Methods We determined the role of Nestin-mediated redox homeostasis and tumor phenotypes in GC cells. Results We found that the Nestin expression level was high in GC tissues and cell lines. Nestin knockdown in the GC cell lines SGC-7901 and MKN-45 reduced viability, induced apoptosis, decreased antioxidant enzyme generation, and repressed GC metastasis. Nestin binds to Keap1, resulting in Nrf2 degradation and influencing downstream gene expression. Nestin knockdown resulted in the downregulation of Nrf2 expression in GC cells. The restoration of Nrf2 expression or treatment with the Nrf2 activator sulforaphane counteracted the inhibitory effect of Nestin knockdown on the proliferation, migration, invasion, and antioxidant enzyme production in GC cells. Moreover, xenograft GC tumors exhibited a slower growth rate than those of the control group in vivo. Conclusions Taken together, these findings suggest that the Nestin–Keap1–Nrf2 axis confers oxidative stress resistance and plays an important role in the proliferation, migration, and invasion of GC cells.